Didactic strategies for creative thinking in high school students: a systematic review - Monteza, Domel (2021)
Creative thinking is the key to adapting to rapidly changing living conditions and providing innovative solutions to various problems, especially in science and technology. The objective of this study was to provide a conceptual basis on didactic strategies and creative thinking, as well as to visualize the implication of the application of various systems in the development of creativity of students in secondary education. The methodology used was the documentary review of 50 articles published in various reliable databases. In addition, the axes of the study proposed as conceptual definitions and didactic strategies for developing creative thinking were taken into account. Finally, it is concluded that if we properly apply didactic methods that develop higher-order skills, there will be more options to increase students' creative thinking.